Women Empowerment through Participation in Self-Help Groups in Bihar, India: A Partial Least Squares Structural Equation Modelling Approach - Kumar, Suman; Sinha, Ashish Ranjan (International Review of Management and Marketing, 2026)
This study makes a modest attempt to examine the impact of participation in self-help groups (SHGs) on women’s empowerment, mainly economic, social, and psychological aspects in Bihar. Led by the JEEViKA initiative, the SHG movement in Bihar has, particularly over the past decade, spread large-scale throughout the rural areas. To put it the other way round, the main motivation leading women to join SHGs is economic benefit. Women who join an SHG are connected to formal financial systems, make savings by using a group account which offers higher interest rates than individual accounts, borrow money from other members at low interest rates, and use government schemes as well as credit institutions for their credit needs. Now this model has profound implications for state socio-economic development, gender equality and poverty reduction. Self-Help Groups that consist mainly of village women from poor backgrounds are important institutional platforms enabling women to overcome the limitations associated with a traditional rural economy. Here, in this research, primary respondents were members of Self Help from the four blocks under Muzaffarpur district and four blocks in Patna District of Bihar State in India. Partial Least Squares structural equation modelling technique has been employed to estimate the relationship. The PLS-SEM results reveal that there is a significant and positive impact of the level of participation of women in SHGs’ activities on their economic, social, and psychosocial empowerment and their overall empowerment as well. Thus, state government and supporting agencies should encourage and organise awareness programs towards more active participation in the SHGs’ activities for further strengthening women’s empowerment